Pedestrian Movement at the Unpaid Concourse Area in KLCC Train Station - Abdul Sukor, Nur Sabahiah (International Journal of Integrated Engineering, 2019)
This study investigates the pedestrian movement during three different peak hours by considering their walking speed and density at the unpaid concourse at a train station. The data for analyses; pedestrian hourly volume and pedestrian walking speed in this study was extracted from the CCTV video footage at the train station in KLCC. The findings show the walking speed at the study area can be considered as fast with the highest walking speed was 1.68m/s during the afternoon peak hour and the slowest walking speed was 0.98m/s during the morning peak hour. The study area was divided into several segments in order to simulate the pedestrian density by using VISWALK. Pedestrian density was highest during the evening peak hours. The study also found that the pedestrian tended to walk in oblique movement to avoid collision with other pedestrian in the crowd during the peak hours. The findings in this study give some insights for pedestrian crowd management in the train station to increase the pedestrian flow and may useful for emergency evacuation planning.